Adsorption of copper(ii) and lead(ii) ions from aqueous solutions by unmodified oil palm shell - Chia, Pui San (2012)
Heavy metals can cause poisoning in living organisms. One of the treatment methods that is economical and environmentally friendly is by adsorption. In this study, the characteristics of adsorbent prepared from spent oil palm shell was analysed and the adsorbent was used for adsorption of Cu(II) and Pb(II) ions. Experiments were conducted through batch adsorption experiments technique to assess the effect of particle size, contact time, agitation rate, dosage, initial adsorbate concentration and initial pH. The residual Cu(II) and Pb(II) ions were detected using atomic absorption spectrometer. The oil palm shell were sieved into various sizes with 27.47% of particles were size 8 < c E 10 mm, 23.26% of particles with size 10 < c E 13 mm and 21.96% with size 6.5 < c E 8 mm. The distribution of oil palm shell particles has uniformity coefficient of less than three indicating potential as filter bed material from hydraulic point of view. Adsorption of Cu(II) and Pb(II) ions could occur in absence of agitation, fulfilling the criteria as filter bed material for slow water feeding system. The pHpzc was found to be at pH 4.1 with maximum adsorption occurred between pH 4.1 to pH 6. Adsorption equilibrium was achieved in 480 min in 150 rpm agitation. Adsorption capacity was enhanced with smaller particle size, lower dosage and higher initial adsorbate concentration. Adsorption isotherms were modeled using Langmuir and Freundlich models and Freundlich model fitted the adsorption data well. This suggested multilayer adsorption manner. The maximum adsorption capacity was found to be 1.76 and 3.39 mg/g for Cu(II) and Pb(II) ions, respectively. Four kinetic models employed in this study were intraparticle diffusion model, expression of Boyd, pseudo-first-order model and pseudo-second-order models. The adsorption data fitted into pseudo-second-order model suggesting occurrence of chemisorption. The results showed that oil palm shell is a potential adsorbent for Cu(II) and Pb(II) ions.